The Reformation of Islamic Thought by Muhammad Abduh and Al-Afghani: Its Implications for Contemporary Da’wah Management - Liddiana, Azzah; Zain, Arifin; Rasyidah; Andrean, Rizky (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
In the nineteenth century, the Muslim ummah faced an intellectual decline exacerbated by colonial domination, creating an urgent need for renewal. This study examines the thoughts of Muhammad Abduh and Jamaluddin al-Afghani through a qualitative library-based approach. The research was conducted in several stages, including data collection from documents related to the thinkers’ ideas, data reduction, analysis, and conclusion drawing. The findings indicate that both figures emphasized rational thought, educational reform, and social awareness. Al-Afghani promoted political mobilization and Muslim solidarity, while Abduh focused on rational theological discourse and institutional educational reform. Their ideas provide a crucial foundation for contemporary da’wah management, and combining al-Afghani’s activist vision with Abduh’s rational reformism can create an organized, adaptive, and effective da’wah strategy that responds to both social and spiritual challenges in modern society.